P677 Patients with Inflammatory Bowel Diseases on anti-TNF treatment have impaired antibody production after Anti-SARS-CoV-2 vaccination: Results from a Panhellenic registry. (21st January 2022) - Zacharopoulou, E; Orfanoudaki, E; Kitsou, V; Tzouvala, M; Tribonias, G; Mantzaris, G J; Viazis, N; Christidou, A; Almpani, F; Karmiris, K; Theodoropoulou, A; Tsafaridou, M; et al.
Abstract: Background: The novel corona virus (SARS-CoV-2) outbreak was declared as a pandemic in March 2020; this prompted the need for rapid vaccine development. Currently four EMA approved vaccines exist but their efficacy and safety data on patients with Inflammatory Bowel diseases are limited. Methods: Greek IBD patients, from 10 tertiary referral centres, who had completed the initial vaccination protocol with the available anti-COVID-19 vaccines at least two weeks before enrolment, were prospectively studied. Demographic and safety data were collected and blood samples were drawn for serum Anti-S1 IgG measurement [Euroimmun Anti-SARS-CoV-2 QuantiVac ELISA (IgG)]. Results: In total 403 IBD patients (59% Crohn's disease, median age 45 years, 53% male) and 124 healthy controls (HC) were included (Table 1). Antibody testing was conducted after a median of 31 (IQR, 23–46) days post-vaccination. Following a full vaccination regimen, 98% of IBD patients seroconverted (anti-S1 IgG≥11 RU/ml). Administration of mRNA vaccines resulted in higher seroconversion rates and higher antibody titers than viral vector ones (98.6% vs 93.6%, P=0.02 and 111.2 RU/ml vs 76 RU/ml, P <0.0001, respectively). In total, IBD patients had lower anti-S1 levels than HC (RU/ml 108 vs 133 RU/ml, P=0.00009). IBD patients without immunosuppression had higher antibody titers than immunocompromised patients ( P =0.012). In univariable analysis, older age, longer time since vaccination, and treatment with corticosteroids, immunomodulators, anti-TNFα or combination therapy were associated with lower anti-S1 titers. In contrast, higher anti-S1 levels were detected in patients on vedolizumab monotherapy or non-immunosuppressive treatment. In multivariable analysis, only age, time since vaccination, and anti-TNFα therapy remained significant ( P =0.011, P =0.002, and P =0.013 respectively). Treatment with vedolizumab monotherapy was associated with higher antibody levels than anti-TNFα or ustekinumab monotherapy ( P =0.023 and P=0.032). Patients with prior COVID-19 infection showed numerically higher levels of Abs. All vaccines were safe in IBD patients. Conclusion: Patients with IBD have high seroconversion rates to anti-SARS-CoV-2 vaccines, with mRNA vaccines being more efficacious. However, IBD patients have impaired response to vaccination comparing to HC. Lower antibody responses were observed in patients who received viral vector vaccines, in older patients, and in those on anti-TNFα treatment. It is important to consider booster vaccination in those low-response groups.